Modeling the effect of loving pedagogy dispositions and teacher self-efficacy on teacher burnout - Chen, Shuya (Frontiers in Psychology, 2023)
Foreign language teaching is a demanding and challenging profession, and teacher burnout is a common issue in this field. There is a growing research interest in exploring the factors that can protect teachers from burnout and promote their well-being, as well as their effectiveness in the classroom. One such factor might be loving pedagogy, which refers to a teacher's positive and compassionate attitudes and behaviors towards their students. This study aimed to examine the association between loving pedagogy, teacher self-efficacy, and teacher burnout among a sample of Chinese English as a foreign language (EFL) teachers. The participants included 428 English teachers from various parts of China. Data on the three constructs were gathered using an electronic survey which comprised three valid questionnaires for these variables. Structural equation modeling (SEM) was used to test the hypothesized relations among the latent constructs. The results indicated that loving pedagogy disposition negatively affected teacher burnout and that teacher self-efficacy mediated the effect of loving pedagogy on burnout. More precisely, higher levels of loving pedagogy were associated with greater levels of teacher self-efficacy, which is in turn negatively affected teacher burnout. These outcomes shed more light on the importance of loving pedagogy dispositions for teachers’ mental health and wellbeing. The discussion and implications for the findings are finally discussed.